Natural rubber-based cushion gum compound formulation at various type and dosage of rubber processing oil and tackifier resin - Santi Puspitasari; Norma Arisanti Kinasih; Arief Ramadhan; Adi Cifriadi; Mochammad Chalid (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2021)
Cold retreading technique dominates retreaded tire manufacturing process. The technique applies rubber cushion gum compound as adhesion medium to bond new tread with a worn old tire. High-quality cushion gum compound mainly requires good adhesive strength. Tackiness of the rubber compound can be improved by addition of tackifier resin and rubber processing oil (RPO). The research was aimed to evaluate the performance of various types and dosages of tackifier resin and bio-based RPO to physic-mechanical properties of cushion gum. A method in the manufacture of natural rubber-based cushion gum compound was in accordance with ASTM D 3182. Cushion gum rubber compound formula was designed by using bio-based RPO such as pine tar oil at 5 and 12 phr and three types of tackifier resin such as rosin resin, phenolic resin, and hydrocarbon resin at 3 and 7 phr. Petroleum-based RPO and commercial cushion gum were selected as reference material. Curing characteristic and physic-mechanical properties test results were used as a reference to determine cushion gum quality. The observation during experiment indicated that natural rubber-based cushion gum compound formulated with addition of 5 phr rosin resin and 5 phr pine tar oil (code ZH4) has the closest curing characteristic and physic-mechanical properties to commercial cushion gum.